The vile village - Snicket, Lemony; Helquist, Brett (New York : HarperCollins, 2001)
Violet, Klaus, and Sunny Baudelaire are wisked off to the village of V.F.D. where a council of elders have enacted thousands of rules about the thousands of crows that inhabit the town and are protected by handyman Hector against Count Olaf, who is after the children's fortune.
Booklist.
New York Times.
School Library Journal.
5.9
5-8
Keywords: Baudelaire, Klaus (Fictitious character) -- Fiction; Baudelaire, Sunny (Fictitious character) -- Fiction; Baudelaire, Violet (Fictitious character) -- Fiction; Brothers and sisters -- Fiction; City and town life -- Fiction; Humorous stories; Orphans -- Fiction; Baudelaire, Klaus (Fictional character) -- Fiction; Baudelaire, Sunny (Fictional character) -- Fiction; Baudelaire, Violet (Fictional character) -- Fiction; City and town life -- Fiction; Humorous fiction; Orphans -- Fiction; Siblings -- Fiction